Ação linguístico-comunicativa e a interação na esfera pública comunicacional - Anecleto, Úrsula Cunha (2016)
The research investigates theoretical basis to support restructuring strategies of linguistic and communicative actions and interaction processes in the public communication in higher education. Research anchored in the Communicative Action Theory of the German philosopher Jürgen Habermas, and the philosophy of language, the linguist Mikhail Bakhtin where the foundations of communicative rationality in communicative action theory and the foundations of the theory of enunciation were studied. He started from the assumption that higher education is the privileged much space to trigger discursive and communicative actions whose pragmatic rationality facilitates consensus-building between speakers and listeners in search of consensus. The thesis substantiates the fact that the university, as fundamental communicational public sphere to society, constitutes a privileged locus for the formation of language subjects, interacting from linguistic and communicative actions, which take into account the relationship Pragmatic Language and Communicative speeches. The methodology used for analysis of selected works was the Hermeneutics. one basic categories framework of the works of both authors who guided exploration of the basic concepts and their co-relations was produced. The study allowed for the interpretation, establish correlations anchored in the understanding of how language-action contributes to increasing the capacity of understanding linguistically communicable way. The university was becoming known as a communicational public sphere important in the context of the network society, to constitute adequate space for interaction between the various social actors that is, free and democratic manner, in order to generate the agreement between them , always from the best argument. To build the theoretical, approach the study was defined as methodological approach to hermeneutics, as it was considered that this approach allows the construction of a critical reflection, anchored in language action. It became clear in the study that the educational subjects in higher education, seeking to develop the ability to understand linguistically communicable way. The analyzes from the categorical framework facilitated dialogue between the two authors with an emphasis on understanding of speech acts, language, concepts of language and communicative competence. The results show that the language in the network society takes on a dimension that requires complex analysis for his understanding, once they emerge broadly new spaces for debates, socialization skills, and consequently the need to transform recurrently information into knowledge. New forms of communication, require the subject to expand its capacity through linguistic and communicative actions, test validity claims about the world and create spaces of dialogue, negotiation and consensus. The study points out forcefully that the language and communicative actions and contribute to the formation of speech acts of ideas, play an important role in the learning process developed in higher education institutions. These actions constitute important mechanisms in the formation of the subject discursively emancipated, free to interact in the public sphere communication from ethical and moral standards, strengthening discursive-rational-dialogical actions.